Synthesis and characterization of new calcium phenylphosphonates and 4-carboxyphenylphosphonates - Svoboda, Jan; Zima, Vítezslav; Benes, Ludvík; Melánová, Klára; Vlcek, Milan (Inorganic chemistry, 2005)
Three new calcium phenylphosphonates, CaC(6)H(5)PO(3).2H(2)O, Ca(3)(C(6)H(5)PO(3)H)(2)(C(6)H(5)PO(3))(2).4H(2)O, and CaC(6)H(5)PO(3).H(2)O, and two calcium 4-carboxyphenylphosphonates, Ca(HOOCC(6)H(4)PO(3)H)(2) and Ca(3)(OOCC(6)H(4)PO(3))(2).6H(2)O, were prepared. It was found that CaC(6)H(5)PO(3).2H(2)O transformed into previously known Ca(C(6)H(5)PO(3)H)(2) via Ca(3)(C(6)H(5)PO(3)H)(2)(C(6)H(5)PO(3))(2).4H(2)O in the presence of phenylphosphonic acid, and vice versa, Ca(C(6)H(5)PO(3)H)(2) turned into CaC(6)H(5)PO(3).2H(2)O in a weak basic medium. A similar relationship was found between Ca(HOOCC(6)H(4)PO(3)H)(2) and Ca(3)(OOCC(6)H(4)PO(3))(2).6H(2)O; i.e., Ca(3)(OOCC(6)H(4)PO(3))(2).6H(2)O transformed into Ca(HOOCC(6)H(4)PO(3)H)(2) in the presence of 4-carboxyphenylphosphonic acid. On the contrary, Ca(3)(OOCC(6)H(4)PO(3))(2).6H(2)O is formed from Ca(HOOCC(6)H(4)PO(3)H)(2) in the presence of ammonium as a weak base. The structure of Ca(HOOCC(6)H(4)PO(3)H)(2) was solved from X-ray powder diffraction data by an ab initio method using a FOX program. The compound is monoclinic, space group C2/c (No. 15), a = 49.218(3) A, b = 7.7609(4) A, c = 5.4452(3) A, beta = 128.119(3) degrees , and Z = 4. Its structure is one-dimensional with [Ca(2)(HOOCC(6)H(4)PO(3)H)(4)](infinity) ribbons forming basic building blocks. The ribbons are held together by hydrogen bonds between carboxylic groups.